2014
DOI: 10.1093/mnras/stu1914
|View full text |Cite
|
Sign up to set email alerts
|

Misaligned accretion on to supermassive black hole binaries

Abstract: We present the results of high-resolution numerical simulations of gas clouds falling onto binary supermassive black holes to form circumbinary accretion discs, with both prograde and retrograde cloud orbits. We explore a range of clouds masses and cooling rates. We find that for low mass discs that cool fast enough to fragment, prograde discs are significantly shorter-lived than similar discs orbiting retrograde with respect to the binary. For fragmenting discs of all masses, we also find that prograde discs … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…A scenario in which SMBHs evolve by accreting individual gas clouds falling from uncorrelated directions has been proposed by King & Pringle (2006). In later publications in the context of BHBs, Nixon and collaborators have shown that this scenario can lead to the formation of counter-rotating discs, facilitating the binary final coalescence (Nixon et al 2011a,b;Dunhill et al 2014;Aly et al 2015). In a somewhat different application, the feeding of SMBHs through individual cloud infall events with different degree of angular momenta randomisation has been proposed as a viable scenario to reproduce current measurement of SMBH spins (Dotti et al 2013;Sesana et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A scenario in which SMBHs evolve by accreting individual gas clouds falling from uncorrelated directions has been proposed by King & Pringle (2006). In later publications in the context of BHBs, Nixon and collaborators have shown that this scenario can lead to the formation of counter-rotating discs, facilitating the binary final coalescence (Nixon et al 2011a,b;Dunhill et al 2014;Aly et al 2015). In a somewhat different application, the feeding of SMBHs through individual cloud infall events with different degree of angular momenta randomisation has been proposed as a viable scenario to reproduce current measurement of SMBH spins (Dotti et al 2013;Sesana et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We set the maximum value of the pericentre distance to rp,max = 2a0, to ensure a transient evolution with the first impact independent of the cloud's relative inclination (see Paper II). Although the exact choice of maximum value is somewhat arbitrary, Dunhill et al (2014) demonstrated that the effect on the binary semimajor axis produced by clouds with larger impact parameters is negligible. Finally, the time difference between events exhibited on Fig. 2 was determined from a Gamma distribution with shape 2 and a scale parameter of θ = 2.5P0.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…Despite these several clues suggesting that stochastic condensation of cold gas and its accretion onto the central MBH is essential for active galactic nuclei, it has been barely explored as a possible source of gas for sub-parsec MBHBs. Notable exceptions are the studies of Dunhill et al (2014), Goicovic et al (2016, hereafter Paper I) and Goicovic et al (2017, hereafter Paper II), where the Authors have numerically modelled the interaction of a single gaseous cloud with MBHBs for a variety of orbital configurations 1 . In particular, Paper II extrapolated the results for these single cloud models to estimate the long-term evolution of a binary interacting with a sequence of near-radial infalling clouds, finding a very efficient shrinking of its orbit.…”
Section: Introductionmentioning
confidence: 99%
“…Accretion on to a MBHB of single clouds has been investigated numerically by Dunhill et al (2014), Goicovic et al (2016) and Goicovic et al (2017), taking into account different orbital configurations and cooling rates. The authors found that the interaction prompts a transient phase of high accretion onto the MBHB, while part of the leftover gas settles into a circumbinary disc of various masses and sizes depending on the initial orbit of the cloud.…”
Section: Introductionmentioning
confidence: 99%